Teaching of science, Technology, Engineering and Mathematics (STEM): A conceptual framework - Riaz, Anum; Awais, Muhammad Taimoor (Advances in Social Sciences Research Journal, 2021)
Conceptual mapping was to study the term gamification in science, technology, engineering, and mathematics (STEM) learning. In total, 287 texts were obtained, of which 39 documents were selected for review. The axes of analysis were: notion, categorization, characterization, differentiation, division, linkage, methodology and exemplification. The result consisted of a systematization of the gamification concept and its methodological aspects for teaching STEM. The main findings will differentiation between gamification, serious educational games, and game-based learning. This will allow planning. The purpose of this documentary research, carried out with the method of Conceptual Cartography, was to make a conceptual study of the term “gamification”, specifically in the learning of science, technology, engineering and mathematics (STEM). A total of 287 texts were obtained and finally 39 documents were selected for revision. Eight axes of analysis were applied: notion, categorization, characterization, differentiation, division, linkage, methodology and exemplification. The result was a systematization of the concept “gamification” and its methodological aspects for the teaching of STEM. The main finding was a differentiation between “gamification”, “educative serious games” and “game-based learning”. This would allow planning differentiated educational strategies according to specific teaching objectives.